DAMPAK PENGELOLAAN KELAS TERHADAP SIKAP DISIPLIN SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Safitri, Dian; Fuadi, Nur (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
The philosophy of Islamic education plays a central role in shaping students' character in schools amid the complex challenges of the modern era, such as globalization, technological advancement, and moral crises. This article aims to examine how fundamental concepts in Islamic educational philosophy can serve as a foundation for developing students who are noble in character, competitive, and relevant to the demands of the times. This study employs a qualitative method with a library research approach and descriptive-analytical analysis. Data were collected from classical and contemporary literature discussing Islamic educational philosophy, including the values of tawhid, akhlak, and the integration of religious and scientific knowledge. The findings reveal that Islamic education based on philosophical principles emphasizes three main aspects: tawhid as a spiritual foundation, akhlak as a moral compass, and knowledge as a means of social transformation. Furthermore, schools hold a strategic role in instilling these values through role modeling, character habituation, and a supportive learning environment. This study highlights the importance of a holistic and adaptive educational approach so that Islamic education in schools can produce graduates who are not only religiously grounded but also responsive to global challenges.